Nosocomial Urinary Tract Infections in Baghdad Teaching Hospital - Najee, eman (Iraqi National Journal of Nursing Specialties, 2011)
Objectives: The objectives of the present study are to identify both, the rate of urinary tract infections (UTI) in medicaland surgical wards in Baghdad Teaching Hospital and the common types of microorganisms that cause this type of NIs,study the resistance of isolated microorganisms to several types of antibiotic and the effect of some disinfectionmaterial like Iodine, chlorhexidine and septicin on the growth of these isolates.Methodology: This is descripƟve study carried out from 1\6\2009 to 1\11\2009. A total of 200 paƟents were admiƩedto medical and surgical wards in Baghdad teaching hospital, paƟents were divided into two group 100 paƟents, insurgical ward and 100 paƟents in medical ward. Some of important information was recorded. Urine samples werecultured on different culture media in order to isolate different pathogenic bacteria. Then, the sensitivity of theseisolates were tested against different antimicrobials, antibiotics (amikacin, ampicillin, cefixime, cefotaxime,cephalexin, gentamycin, nalidixic acid, nitrofuranion, rifimpicin and vancomycin) and the effects of differentdisinfectant solutions with different concentrations; including benzalkonium chloride (septicin, commercial),chlorhexidine and povidoniodine (betadine, commercial), were tested as well on the growth of isolated bacteria.Results: The results show that a high incidence of (UTI) as nosocomial infections appeared in medical and surgicalwards in Baghdad Teaching Hospital and most of paƟents were male at age groups ranged from 46-55 years and 36-45years in medical and surgical ward respectively. The highest rate of UTIs increased in patients who had neededcatheterization procedures in both wards. Gram negative bacteria were commonly p. aeuroginosa and E. coli, lesscommonly gram positive bacteria like methicillin-resistant Satph aureus were isolated as etiologic agents of UTIsinfections in both wards. Moreover, multi-drug resistance for common use antibiotics was observed in most virulentspecies like Pseudomonas aeuroginos and Methicillin resistant Staphylococcus aureus (MRSA). Nitrofurantion was thebest drug for all bacterial isolates. It was obvious that 10-15% of povidione-iodine solution has more effect on thegrowth controlling of pathogenic bacteria, especially Pseudomonas aeuroginos isolates. The results indicatedsignificant differences (p˂0.01) between the effect of SepƟcin and Chlorhexidine on the acƟvity of isolated bacteria.Recommendations: The study recommends that the catheter should be changed every 2 days, especially if signs ofurinary tract infections appear and using antimicrobial catheters and intelligent use of aseptic techniques, and limitingthe use of antibiotics and the use of most effective disinfectant in the exact concentration specified by themanufacture, and the detection antibiotic resistance gene using Polymerase Chain Reaction (PCR) technique.